Determinaciones fisicoquímicas de las hojas secas de piper aduncum (matico) procedente de la provincia de San Marcos - Cajamarca - 2013 - Polo Vidal, Milagros Elizabeth (2015)
The purpouse of this work is to determine physicochemical characteristics of the dried leaves of Piper aduncum from the province of San Marcos – Departament Cajamarca. The dried leaves of Piper aduncum were collected in August 2013, I was selected dried and ground stored at the temperature of 40° Celsius and then sieved using N° 17 sieve. Sample were in ambar bottles for posterior use. It was determined in the dried leaves of Piper aduncum, ashes: 11,35 % ± 0.54 total ashes, 6,24% ± 1,54 soluble water ashes and 4,95% ± 0.04 insoluble in hydrochloric acid ashes